2015
DOI: 10.1590/0001-3765201520150008
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover markers for early detection of fracture healing disturbances: A review of the scientific literature

Abstract: Imaging techniques are the standard method for assessment of fracture healing processes. However, these methods are perhaps not entirely reliable for early detection of complications, the most frequent of these being delayed union and non-union. A prompt diagnosis of such disorders could prevent prolonged patient distress and disability. Efforts should be directed towards the development of new technologies for improving accuracy in diagnosing complications following bone fractures. The variation in the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 50 publications
(65 reference statements)
5
40
0
Order By: Relevance
“…So the third group and the second group are the better fractured bone healing than the first group, depending on the serial rates of alkaline phosphatase enzyme concentrations in serum. This is confirmed by Kanwar et al and Sousa et al (27,28), they said that, the high levels of alkaline phosphatase in the serum indicated to the activity of osteoblast cells, and new bone formation. There was no significant difference in concentrations rates of calcium in the three main groups despite the increasing in concentrations in the weeks followed the operation.…”
Section: Discussionsupporting
confidence: 56%
“…So the third group and the second group are the better fractured bone healing than the first group, depending on the serial rates of alkaline phosphatase enzyme concentrations in serum. This is confirmed by Kanwar et al and Sousa et al (27,28), they said that, the high levels of alkaline phosphatase in the serum indicated to the activity of osteoblast cells, and new bone formation. There was no significant difference in concentrations rates of calcium in the three main groups despite the increasing in concentrations in the weeks followed the operation.…”
Section: Discussionsupporting
confidence: 56%
“…A similar picture is described by authors who reviewed the role and potential of biochemical serum markers as indicators of fracture healing disturbances [33, 34, 36, 50, 51]. In theory, the above molecules could reflect a poor response to the regenerative treatment, but this cannot be ascertained in our study because of the lack of failed cases.…”
Section: Discussionsupporting
confidence: 68%
“…BTMs could provide important information concerning bone metabolism at a systemic level, namely about bone remodelling process during induction of osteoporosis and its treatment in experimental orthopaedic studies. Recently it was developed a study by Baharuddin et al (2014) in sheep with osteoclast regulatory proteinreceptor activator of nuclear factor NF-κB ligand (RANKL) produced by osteocytes, osteoblasts and immune system cells, its membrane-bound receptor (RANK) in the osteoclast precursor cells and osteoprotegerin (OPG) as new potential bone markers in future (Sousa et al 2015), nevertheless more studies would be necessary to assess the usefulness of BTMs in this scientific field. …”
Section: Discussionmentioning
confidence: 99%